Assessing sustainable urban development based on functional spatial differentiation of urban agriculture in Wuhan, China. (April 2022) - Wang, Min; Yuan, Mengchu; Han, Pingyang; Wang, Dan
Abstract: Harmonized development of urban agricultural functions is necessary to ensure sustainable urban development, in which rational utilization of land plays a key role. With rapid urbanization, urban agricultural land has been encroached, the development of urban agriculture functions has become unbalanced, and differences between land, agriculture, and urban systems have become more evident. In this study, we analyzed the characteristics of land use structure and the functional spatial differentiation of urban agriculture in Wuhan and studied the quantitative relationship and influence mechanisms between them. We found that the spatial differentiation of urban agricultural function in Wuhan was closely related to the urban developmental structure, comprehensive index of land use degree, and information entropy of land use structure; moreover, urban agricultural land rate showed different effects on urban agricultural functions of different clusters. Based on these results, we proposed optimization strategies for streets and towns with different development levels of urban agricultural functions to promote sustainable development of both urban agriculture and cities through the rational use of land. Highlights: Functional spatial differentiation and land use of urban agriculture were studied. Urban agricultural functions represented typical spatial differentiation. Land use structure showed varying effects on urban agricultural functions. Strategies were proposed for sustainable urban development and urban agriculture.